1981
DOI: 10.1111/j.1365-2133.1981.tb08172.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the incidence of auto-immune disorders in patients with lichen sclerosus and atrophicus

Abstract: Patients with lichen sclerosus and atrophicus have an increased incidence of organ specific antibodies, and these patients and their relatives have a significantly higher incidence of associated autoimmune diseases than a control population. The incidence of other auto-immune diseases in patients with lichen sclerosus is highest when the onset is between the ages of 41 and 60 years, but is not related to the duration or site of the lesions. These findings suggest an immunological basis for the disease and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
1
9

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(100 citation statements)
references
References 1 publication
6
82
1
9
Order By: Relevance
“…For example, some reports have described a disease association with HLA class II antigen DQ7-DQ9 (7,8), as well as an increased incidence of other autoimmune diseases and autoantibodies in some patients. Associated disorders include thyroid disease, pernicious anemia, diabetes mellitus, alopecia areata, vitiligo, and mucous membrane pemphigoid (1,4,9). Historically, data implicating a humoral autoimmune response in lichen sclerosus have been limited to a single 90-year-old case report of probable lichen sclerosus being induced by injection of serum from an affected individual into nonlesional skin (10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some reports have described a disease association with HLA class II antigen DQ7-DQ9 (7,8), as well as an increased incidence of other autoimmune diseases and autoantibodies in some patients. Associated disorders include thyroid disease, pernicious anemia, diabetes mellitus, alopecia areata, vitiligo, and mucous membrane pemphigoid (1,4,9). Historically, data implicating a humoral autoimmune response in lichen sclerosus have been limited to a single 90-year-old case report of probable lichen sclerosus being induced by injection of serum from an affected individual into nonlesional skin (10).…”
Section: Introductionmentioning
confidence: 99%
“…4 The evidence for an increased association with other autoimmune disorders is thus far weak. One small controlled study 2 compared the prevalence of autoimmune disorders and serum autoantibodies in 50 patients with LS and 50 healthy controls and found an increased prevalence of both autoimmune disorders and autoantibodies in those with LS. A larger study of 350 women with LS did not have a control group 1 but reported a high prevalence of associated autoimmune disorders (21%).…”
mentioning
confidence: 99%
“…Choroby autoimmunologiczne towarzyszące LS opisywano częściej u kobiet (19-54%) niż u męż-czyzn (3-5%) [7][8][9][10][11][12][13][14][15]. U niektórych kobiet LS współ-występował z bielactwem, łysieniem plackowatym, nietolerancją glukozy czy anemią złośliwą.…”
Section: Obraz Klinicznyunclassified